Respostas
respondido por:
45
(x + y)² = 64
x² + 2xy + y² = 64
x² + y² + 2xy = 64
Como x² + y² = 34
34 + 2xy = 64
2xy = 64 - 34
2xy = 30 (x3)
6xy = 90
x² + 2xy + y² = 64
x² + y² + 2xy = 64
Como x² + y² = 34
34 + 2xy = 64
2xy = 64 - 34
2xy = 30 (x3)
6xy = 90
Anônimo:
Adriel, de onde surgiu o 32?
respondido por:
60
x^2 + y^2 = 34 (1)
(x + y)^2 = 64 (2)
Desenvolvendo produto notável
x^2 + y^2 + 2xy = 64
(1) no desenvolvimento
34 + 2xy = 64
2xy = 64 - 34
2xy = 30
xy = 15
6xy = 6.15
6xy = 90
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás